The Implementation Of The Card Shift Method In PAI Learning Questions In Class V SDN 09 VII Koto Sungai Sarik Padang Pariaman - Muliyarti Muliyarti (Program Pascasarjana UMSB, 2021)
The trend in education today is to restore the point of view of student success in learning that will be successful if a conducive environment is created. Learning material will be easy to remember if students play a direct role in learning, not just listeners. In the past, students were often burdened with target material to train their memory. However it worked in the short term. Their memory will disappear over time. But things like this make students fail in solving problems every day.The core of the discussion that will be discussed in this research is,